INTERACTION OF COMPONENTS IN THE La-Li-Ni-Si SYSTEM AT A TEMPERATURE OF 400ºС - Стецьків, Андрій; Гаврищук, Любомир (SWorldJournal, 2024)
The interaction of the components in the La Li Ni Si system in the LaSi LiSi Ni Si region was investigated by X-ray phase, local X-ray spectral analyses and microstructural analysis methods at 400ºC. The alloys were prepared by arc melting of stoichiomet